2008
DOI: 10.1021/cg700967y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of BaMoO4 Nestlike Nanostructures Under a New Growth Mechanism

Abstract: Novel BaMoO4 nestlike nanostructures assembled with single-crystal nanosheets have been successfully synthesized by using PVP (K30) as capping reagents under hydrothermal conditions. Detailed proofs indicated that the process of crystal growth was dominated by a crystallization−dissolution−recrystallization−self-assembly growth mechanism. The morphology of BaMoO4 evolved from several micro-compressed decahedrons to two-dimensional (2-D) nanoplates and to three-dimensional (3-D) nestlike nanostructures. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 35 publications
5
59
0
Order By: Relevance
“…In previous studies, 9 we suggested that the growth of ZnS obtained by MAS can be described via a nucleationdissolution-recrystallization mechanism, and this mechanism is responsible for the fast nucleation of the ZnS small particles which aggregate into a spherical morphology to minimize their surface energy. In general, the nucleation-dissolutionrecrystallization mechanism occurs using the MAS method, 9,38,40,64 which is considered highly sensitive to relative rates of amorphous solid particle dissolution and nucleation of the crystalline phase. 17,38,[64][65][66][67][68] As a consequence, this mechanism involves the formation of a high concentration of aggregated nanoparticles with predominant growth controlled by the coalescence process.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, 9 we suggested that the growth of ZnS obtained by MAS can be described via a nucleationdissolution-recrystallization mechanism, and this mechanism is responsible for the fast nucleation of the ZnS small particles which aggregate into a spherical morphology to minimize their surface energy. In general, the nucleation-dissolutionrecrystallization mechanism occurs using the MAS method, 9,38,40,64 which is considered highly sensitive to relative rates of amorphous solid particle dissolution and nucleation of the crystalline phase. 17,38,[64][65][66][67][68] As a consequence, this mechanism involves the formation of a high concentration of aggregated nanoparticles with predominant growth controlled by the coalescence process.…”
Section: View Article Onlinementioning
confidence: 99%
“…In general, the nucleation-dissolutionrecrystallization mechanism occurs using the MAS method, 9,38,40,64 which is considered highly sensitive to relative rates of amorphous solid particle dissolution and nucleation of the crystalline phase. 17,38,[64][65][66][67][68] As a consequence, this mechanism involves the formation of a high concentration of aggregated nanoparticles with predominant growth controlled by the coalescence process. 39 EDXS reveals that the products contain Zn and S which are in excellent agreement with the stoichiometry of ZnS, indicating the purity of the sample processed by the MAS method.…”
Section: View Article Onlinementioning
confidence: 99%
“…Recently, alkaline earth molybdate materials with a scheelite-type structure have attracted much interest because of their luminescent behavior, electro-optical properties, structural properties and potential applications [1][2][3]. The green luminescence properties of molybdate of relatively large bivalent cations (Ca, Ba, Pb and Sr with ionic radii >0.99Å) have attracted much attention of many researchers due to their applications in electro-optical industries [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…The green luminescence properties of molybdate of relatively large bivalent cations (Ca, Ba, Pb and Sr with ionic radii >0.99Å) have attracted much attention of many researchers due to their applications in electro-optical industries [2,4]. Among the molybdate materials, BaMoO 4 with a scheelite structure is an important material in electro-optics, due to its production of blue, green and orange luminescence, and in electro-optical applications, including solid-state lasers and optical fibers [3,5,6]. * E-mail: phuruangrat@hotmail.com In this research, the shuttle-like BaMoO 4 microstructures have been synthesized by microwave method.…”
Section: Introductionmentioning
confidence: 99%
“…This method generally leads to a cost reduction due to low synthesis temperatures; it also promotes high yield reactions and enables large volume processing [1,2,15]. In a recent study, Luo et al [17] reported BaMoO 4 nest-like nanostructures prepared under hydrothermal conditions. Particles with a controllable size and shape, high crystallinity and low agglomeration can be obtained using this synthetic route [1,2].…”
Section: Introductionmentioning
confidence: 99%